The Development of the Number of Pupils in Secondary Institutions in Light of Political and School Structure Changes - Gabriella Józsa (Debrecen University Press, 2020)
There are a number of factors around the world that influence the evolution of school structure such as historical, cultural tradition, nature of the economy, demographics, etc. After-primary school further education is a highlight of the Hungarian school system, as it also defines the entire school career and future of the pupils. The choice between the three types of training, the secondary school, vocational academic school and standard vocational school, is backed by different strategies spanning the entire school career of the students, the educational qualifications being the goal. While choosing high school leads to a degree, the choice of vocational school is one of the fastest and easiest ways of the acquisition of qualifications. However, vocational secondary school also offers a chance to study in higher education (Hermann, 2005) In our study, we look at the evolution of secondary school types in light of policy changes from the 1940s to the present day.